Ultrafast microsphere near-field nanostructuring - Leitz, Karl-Heinz; Quentin, Ulf-Hermann; Hornung, B.; Otto, Andreas; Alexeev, Ilya; Schmidt, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2011)
Due to the steadily advancing miniaturization in all fields of technology nanostructuring becomes increasingly important. Whereas the classical lithographic nanostructuring suffers from both high costs and low flexibility, for many applications in biomedicine and technology laser based nanostructuring approaches, where near-field effects allow a sub-diffraction limited laser focusing, are on the rise. In combination with ultrashort pulsed laser sources, that allow the utilization of non-linear multi-photon absorption effects, a flexible, low-cost laser based nanostructuring with sub-wavelength resolution becomes possible. Among various near-field nanostructuring approaches the microsphere based techniques, which use small microbead particles of the size of the wavelength for a sub-diffraction limited focusing of pulsed laser radiation, are the most promising. Compared to the tip or aperture based techniques this approach is very robust and can be applied both for a large-scale production of periodic arrays of nanostructures and in combination with optical trapping also for a direct-write. Size and shape of the features produced by microsphere near-field nanostructuring strongly depend on the respective processing parameters. In this contribution a basic study of the influence of processing parameters on the microsphere near-field nanostructuring with nano-, pico- and femtosecond laser pulses will be presented. The experimental and numerical results with dielectric and metal nanoparticles on semiconductor and dielectric substrates show the influence of particle size and material, substrate material, pulse duration, laser fluence, number of contributing laser pulses and polarization on the structuring process. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
Created from Fastlane, Scopus look-up
Keywords: microsphere near-field nanostructuring; multi-photon absorption; near-field effects; Ultrafast material processing